Evaluation of a smartphone for telepathology: Lessons learned - Paul Fontelo; Fang Liu; Yukako Yagi (Elsevier, 2015)
Background: Mobile networks and smartphones are growing in developing countries. Expert telemedicine consultation will become more convenient and feasible. We wanted to report on our experience in using a smartphone and a 3-D printed adapter for capturing microscopic images. Methods: Images and videos from a gastrointestinal biopsy teaching set of referred cases from the AFIP were captured with an iPhone 5 smartphone fitted with a 3-D printed adapter. Nine pathologists worldwide evaluated the images for quality, adequacy for telepathology consultation, and confidence rendering a diagnosis based on the images viewed on the web. Results: Average Likert scales (ordinal data) for image quality (1=poor, 5=diagnostic) and adequacy for diagnosis (1=No, 5=Yes) had modes of 3 and 4, respectively. Adding a video overview of the specimen improved diagnostic confidence. The mode of confidence in diagnosis based on the images reviewed was four. In 31 instances, reviewers' diagnoses completely agreed with AFIP diagnosis, with partial agreement in 9 and major disagreement in 5. There was strong correlation between image quality and confidence (r = 0.78), image quality and adequacy of image (r = 0.73) and whether images were found adequate when reviewers were confident (r = 0.72). Intraclass Correlation for measuring reliability among the four reviewers who finished a majority of cases was high (quality=0.83, adequacy= 0.76 and confidence=0.92). Conclusions: Smartphones allow pathologists and other image dependent disciplines in low resource areas to transmit consultations to experts anywhere in the world. Improvements in camera resolution and training may mitigate some limitations found in this study.